2021
DOI: 10.1097/meg.0000000000002034
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced liver injury in coronavirus disease-2019 (COVID-19): untangling the knots

Abstract: Liver dysfunction manifesting as elevated aminotransferase levels has been a common feature of coronavirus disease-2019 (COVID-19) infection. The mechanism of liver injury in COVID-19 infection is unclear. However, it has been hypothesized to be a result of direct cytopathic effects of the virus, immune dysfunction and cytokine storm-related multiorgan damage, hypoxia-reperfusion injury and idiosyncratic drug-induced liver injury due to medications used in the management of COVID-19. The favored hypothesis reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 117 publications
0
15
0
1
Order By: Relevance
“…TNF-α is a pyrogenic cytokine secreted by macrophages, monocytes, Th1 cells, Th17 cells, CD8 + T cells, and DCs during the acute phase of inflammation or infection ( 68 , 77 , 79 ). It is a central cytokine in viral diseases that increases vascular permeability ( 251 ) and is associated with several chronic inflammatory conditions and autoimmune diseases ( 68 ). For >20 years now, anti-TNF antibodies have been used for alleviating the severity of some autoimmune inflammatory diseases, including rheumatoid arthritis, inflammatory bowel disease, and ankylosing spondylitis.…”
Section: Cytokine Secretion Induced By Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α is a pyrogenic cytokine secreted by macrophages, monocytes, Th1 cells, Th17 cells, CD8 + T cells, and DCs during the acute phase of inflammation or infection ( 68 , 77 , 79 ). It is a central cytokine in viral diseases that increases vascular permeability ( 251 ) and is associated with several chronic inflammatory conditions and autoimmune diseases ( 68 ). For >20 years now, anti-TNF antibodies have been used for alleviating the severity of some autoimmune inflammatory diseases, including rheumatoid arthritis, inflammatory bowel disease, and ankylosing spondylitis.…”
Section: Cytokine Secretion Induced By Sars-cov-2 Infectionmentioning
confidence: 99%
“…GM-CSF further induces CD14 + CD16 + inflammatory monocytes to produce increased IL-6 ( 368 , 369 ). This could activate more macrophages and contribute to an inflammatory storm ( 251 , 368 , 369 ). This immune-mediated injury, accompanied by elevated concentrations of IL-1, IL-2, IL-10, and IFNγ, would lead to systemic inflammatory response syndrome (SIRS) ( 368 , 369 ).…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…The mechanism of liver injury in COVID-19 infection is postulated to be a result of direct cytopathic effects of the virus; immune imbalance and cytokine storm-related multiorgan damage; hypoxia-reperfusion dysfunction; and idiosyncratic, drug-induced liver injury due to medications used for the management of COVID-19 infection [30,31]. Early retrospective data from China and Italy showed that elevated inflammatory markers-particularly ferritin, CRP, LDH, interleukin 6 [IL-6], and D-dimer-were associated with severe illness and increased mortality [32].…”
Section: Discussionmentioning
confidence: 99%
“…Early retrospective data from China and Italy showed that elevated inflammatory markers-particularly ferritin, CRP, LDH, interleukin 6 [IL-6], and D-dimer-were associated with severe illness and increased mortality [32]. A severely dysregulated immune response to local inflammation (COVID-19-induced pneumonia) with heightened production of cytokines and chemokines that in turn act as chemoattractants for other inflammatory cells result in an exaggerated immune response with consequent systemic manifestations and multi-organ involvement [30]. This sequence of events, termed cytokine storm, has been shown to be a major determinant of poor survival in patients with COVID-19 infection [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation